Reptiles and Amphibians 2018
DOI: 10.5772/intechopen.76647
|View full text |Cite
|
Sign up to set email alerts
|

Sea Turtle Beach Monitoring Program in Brazil

Abstract: Beach monitoring programs provide important information on spatial and temporal patterns of occurrence, mortality, age structure, sex ratio, and variations associated with climatic and anthropogenic events as well as for the assessment of the health of marine organisms. The purpose of the Santos Basin Beach Monitoring Project is to evaluate the possible effects of oil and gas production and transport activities at Santos Basin on marine turtles, birds, and mammals by monitoring beaches and veterinary care faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Three beach monitoring programmes (BMPs) monitored the entire coast of Rio de Janeiro state (approximately 1317 km) and recorded stranded sea turtles throughout the study period. The BMPs were authorized by the Brazilian Institute for the Environment and Renewable Natural Resources (IBAMA/MMA), as required by federal environmental licensing of PETROBRAS activities for the production and disposal of oil and natural gas in the Santos and Campos Basin (PETROBRAS, ; Werneck et al, ), except in the municipalities of Campos dos Goytacazes and São João da Barra (22°05′34.8′′ S 41°08′03.8′′ W to 21°37′09.1′′ S 41°00′53.3′′ W; 66 km of extension), where the BMP was associated with the state licensing of Açu Port. All BMPs featured daily patrols for stranded sea turtles, and also involved a collaborative stranding network, in which beach cleaners, public agencies and the local citizens contacted the BMPs to collect stranded turtles (see Werneck et al () for more information).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three beach monitoring programmes (BMPs) monitored the entire coast of Rio de Janeiro state (approximately 1317 km) and recorded stranded sea turtles throughout the study period. The BMPs were authorized by the Brazilian Institute for the Environment and Renewable Natural Resources (IBAMA/MMA), as required by federal environmental licensing of PETROBRAS activities for the production and disposal of oil and natural gas in the Santos and Campos Basin (PETROBRAS, ; Werneck et al, ), except in the municipalities of Campos dos Goytacazes and São João da Barra (22°05′34.8′′ S 41°08′03.8′′ W to 21°37′09.1′′ S 41°00′53.3′′ W; 66 km of extension), where the BMP was associated with the state licensing of Açu Port. All BMPs featured daily patrols for stranded sea turtles, and also involved a collaborative stranding network, in which beach cleaners, public agencies and the local citizens contacted the BMPs to collect stranded turtles (see Werneck et al () for more information).…”
Section: Methodsmentioning
confidence: 99%
“…This analysis focused on the coast of Rio de Port. All BMPs featured daily patrols for stranded sea turtles, and also involved a collaborative stranding network, in which beach cleaners, public agencies and the local citizens contacted the BMPs to collect stranded turtles (see Werneck et al (2018) for more information).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stranded turtles were found and reported by local residents and fishermen. Thereafter, staff from the Marine Animal Research and Rescue Centre of Walailak University or the Marine and Coastal Resources Research Centre went to retrieve the turtles in order to investigate the cause of stranding and health status or cause of death according to standard protocols (Work 2000, Flint et al 2009, Werneck et al 2018. For dead turtles, the carcass condition was categorised to fresh, evident decomposition, advanced decomposition, or mummified (Werneck et al 2018).…”
Section: Data Of Stranded Sea Turtlementioning
confidence: 99%
“…All species found in Brazil are threatened, varying between vulnerable (Caretta caretta Linnaeus, 1758, Dermochelys coriacea Vandelli, 1761 and Lepidochelys olivacea Eschscholtz, 1829), endangered (Chelonia mydas Linnaeus, 1758) and critically endangered (Eretmochelys imbricata Linnaeus, 1766), according to International Union for Conservation of Nature (IUCN 2021) or the Brazilian Red Book of Threatened Species of Fauna (Chico Mendes Institute for Biodiversity Conservation/ Ministry of Environment -ICMBio/MMA 2018). These five species frequent the coast of the State of Rio de Janeiro (Santos et al 2011;Reis et al 2017;Werneck et al 2018;Tagliolatto et al 2019a), a region identified as an important spawning site for the C. caretta (Marcovaldi and Chaloupka 2007) and a foraging habitat, mainly for juveniles of C. mydas (Almeida et al 2011;Awabdi et al 2013;Reis et al 2017;Guimarães et al 2018;Tagliolatto et al 2019a).…”
Section: Introductionmentioning
confidence: 99%